Pengaruh Pengaturan Suhu Penggorengan Vacum Terhadap Sifat-Sifat Kimia Keripik Salak (Salaca edulis Reinw) - Rachel Breemer; Syane Palijama; Febry R Palijama (AGRITEKNO: Jurnal Teknologi Pertanian, 2018)
Snake fruit (Salaca edulis Reinw) has a taste of sweet and sour, with a strong astringent edge. Snake fruit can be processed into chips in order to prolong its shelf life. Fruit chips processed with vacuum frying technology does not compromise the form, taste, colour, and aroma of the native fruits. However, in an effort to obtain crisp and tasteful snake fruit chips, the temperature of the vacuum frying process should be adjusted accordingly. Results showed the frying temperature of 70°C resulted in the chips which had Vitamin C, total acidity, and moisture contents of 0.11 mg, 16.05%, and 12.74%, respectively. When chips were fried with 80°C, the resulting product had a Vitamin C of 0.12 mg, total acidity of 16.14%, and moisture of 14.02%. Whereas chips with lower Vitamin C, total acidity, and moisture contents of 0.09 mg, 8,54%, and 6.01%, subsequently resulted from frying with 90°C. Keywords: chips, snake fruits, vacuum frying